A Study of Nil Ideals and Kothe’s Conjecture in Neutrosophic Rings - Mohammad Abobala (International Journal of Mathematics and Mathematical Sciences)
The aim of this study is to determine the necessary and sufficient condition for any AH subset to be a full ideal in a neutrosophic ring R(I) and to be a nil ideal too. Also, this work shows the equivalence between Kothe’s conjecture in classical rings and corresponding neutrosophic rings, i.e., it proves that Kothe’s conjecture is true in the neutrosophic ring R(I) if and only if it is true in the corresponding classical ring R.